Thrust test stand for pulse jet engine / Hamirul Adli Hashim - Hashim, Hamirul Adli (2004)
One of the important performance parameters of a pulse jet engine is the thrustproduced. Hence, for any new design, the measurement of the thrust produced isnecessary. A test stand was successfully designed and fabricated from scratch usingfacilities available in the FKM's workshop. The test stand was designed for a pulse jetengine with maximum thrust of 25 N.The design concept was based on balancing the moment due to the thrust of thepulse jet engine with a dead weight which is movable so as to provide a counter-moment.